2022
DOI: 10.1088/2053-1591/ac4fdf
|View full text |Cite
|
Sign up to set email alerts
|

Improving the stability of nanofluids via surface-modified titanium dioxide nanoparticles for wettability alteration of oil-wet carbonate reservoirs

Abstract: The main challenge of the application of nanofluids for enhanced oil recovery (EOR) in oil-wet carbonate reservoirs is maintaining their stability under high-temperature and high-salinity which is normally seen in reservoir conditions. In this work, surface-modified TiO2 nanoparticles were synthesized by N-(2-Aminoethyl)-3-Aminopropyltrimethoxysilane (AEAPTMS) as a coupling agent for surface modification of nanoparticles. Zeta potential and dynamic light scattering analyses were used to evaluate the stability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…TiO 2 is typically applied in the field of photosensitive materials. However, recent research by Hosseini et al [21] has shown that nanofluids prepared using TiO 2 can alter the wettability of rocks. In this study, surface-modified TiO 2 NPs were prepared using coupling agents, and nanofluids prepared with these NPs were used to treat the rock surfaces.…”
Section: Inorganic Nanofluidsmentioning
confidence: 99%
“…TiO 2 is typically applied in the field of photosensitive materials. However, recent research by Hosseini et al [21] has shown that nanofluids prepared using TiO 2 can alter the wettability of rocks. In this study, surface-modified TiO 2 NPs were prepared using coupling agents, and nanofluids prepared with these NPs were used to treat the rock surfaces.…”
Section: Inorganic Nanofluidsmentioning
confidence: 99%
“…Targeting ligands are molecules that can selectively bind to receptors or antigens that are overexpressed on the surface of target cells, thereby directing nanoparticles to specific tissues or cells [55]. The selection of targeting ligand depends on the target receptor and desired pharmacokinetic properties.…”
Section: Targeting Ligandsmentioning
confidence: 99%
“…Recently, the use of nanoparticles (NPs) has received widespread attention for its potential EOR applications. NPs are particles typically ranging from 1 to 100 nm in size. Several types of nanomaterials have been studied for application in EOR, including titanium dioxide, ,, graphene, silica dioxide, , aluminosilicate, zirconium dioxide, ,, and silica dioxide in the CO 2 -brine system. , Laboratory investigations have demonstrated that the surfactant performance can be enhanced by combining the surfactant solution with nanomaterials to improve the interfacial properties between the oil–water-rock system. ,,,,, Nourinia et al . reported that adding zinc oxide/monmorillonite nanocomposites into a natural surfactant derived from cyclamen persicum reduced the IFT to a minimum of 2.5 mN/m.…”
Section: Introductionmentioning
confidence: 99%
“… 14 18 NPs are particles typically ranging from 1 to 100 nm in size. 19 25 Several types of nanomaterials have been studied for application in EOR, including titanium dioxide, 18 , 24 , 26 graphene, 22 silica dioxide, 23 , 27 30 aluminosilicate, 31 zirconium dioxide, 16 , 32 , 33 and silica dioxide in the CO 2 -brine system. 34 , 35 Laboratory investigations have demonstrated that the surfactant performance can be enhanced by combining the surfactant solution with nanomaterials to improve the interfacial properties between the oil–water-rock system.…”
Section: Introductionmentioning
confidence: 99%